Gastric Mucinous Cancer Histology: Clinicopathological Characteristics and Prognostic Value. (29th December 2015) - Jian-Hui, Chen; Shi-Rong, Cai; Hui, Wu; Jian-bo, Xu; Kai-Ming, Wu; Si-le, Chen; He, Yu-Long
Abstract : MC tended toward worse tumor biological behavior and long-term survival outcome compared to WMDC. Moreover, MC also showed worse clinicopathological features and survival outcome in some selected patients. For these reasons, MC should be deemed as a special histological type of gastric cancer with worse clinicopathological features and survival outcome.